IT Systems Supporting Finance and Accounting - Wyslocka, E. (Электронное моделирование, 2009)
The paper contains a description of IT needs of mid-sized companies in the area of financial and accounting software. Activities undertaken on particular stages of acquiring new IT system and associated problems and the most relevant requirements, which should be met by financial and accounting software used to keep the books of accounts, were also discussed. These requirements are strictly defined in the Accounting Act, however a transcription on the IT language and adjustment of created software reveal many unexpected problems. The most common difficulties are discussed in this paper.